Implementasi Forensik Digital dalam Hukum Syariah - Grace Yulianti; Ngadi Permana (Universitas Kristen Indonesia Toraja, 2024)
This study aims to explore the application of digital forensics in the Sharia law system, focusing on the challenges and solutions that arise in the acceptance of digital evidence. Sharia law tends to prioritize physical evidence, such as witnesses and written documents, making abstract digital evidence face difficulties in being accepted. Key challenges include insufficient infrastructure, the misalignment between Sharia law principles and digital technology, and limited training for legal practitioners. However, there are opportunities to improve the acceptance of digital evidence through regulatory updates, intensive training, and the development of clear guidelines. The implementation of digital forensics can strengthen law enforcement, especially in cybercrime cases that are difficult to trace with traditional evidence.